SPACE ARCHAEOLOGIST. - TUCKER, ABIGAIL (Smithsonian, 2016)
The article discusses the efforts by University of Alabama at Birmingham anthropology professor Sarah Parcak and her team to find long-buried treasures through the use of satellite imagery and other remote sensing tools as of December 2016. Among the accomplishments of Parcak's team are the discovery of ancient settlements, pyramids, and lost tombs. Also cited is the team's current project called GlobalXplorer involving the satellite-mapping of Peru.